2016
DOI: 10.1002/2015jb012136
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory observations of time‐dependent frictional strengthening and stress relaxation in natural and synthetic fault gouges

Abstract: Interseismic recovery of fault strength (healing) following earthquake failure is a fundamental requirement of the seismic cycle and likely plays a key role in determining the stability and slip behavior of tectonic faults. We report on laboratory measurements of time‐ and slip‐dependent frictional strengthening for natural and synthetic gouges to evaluate the role of mineralogy in frictional strengthening. We performed slide‐hold‐slide (SHS) shearing experiments on nine natural fault gouges and eight syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
121
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(153 citation statements)
references
References 141 publications
(299 reference statements)
24
121
4
Order By: Relevance
“…In the laboratory, during the early part of the interseismic period, immediately after the stress drop, wave speed increases and reaches approximately the preslip value within a short time (Figures ). The increase in V p is consistent with log‐time growth, and/or stiffening, of grain contact junctions, consistent with frictional healing [e.g., Scuderi et al ., ; Carpenter et al ., ]. We note that similar observations have been made on natural faults [ Vidale and Li , ; Brenguier et al ., ; Taira et al ., ].…”
Section: Discussionsupporting
confidence: 87%
“…In the laboratory, during the early part of the interseismic period, immediately after the stress drop, wave speed increases and reaches approximately the preslip value within a short time (Figures ). The increase in V p is consistent with log‐time growth, and/or stiffening, of grain contact junctions, consistent with frictional healing [e.g., Scuderi et al ., ; Carpenter et al ., ]. We note that similar observations have been made on natural faults [ Vidale and Li , ; Brenguier et al ., ; Taira et al ., ].…”
Section: Discussionsupporting
confidence: 87%
“…[] and Carpenter et al . [] reported about 11 and 16% weight loss during drying, respectively. For wet experiments, a room dry sample was jacketed and placed in a pressure vessel with a small confining pressure.…”
Section: Methodsmentioning
confidence: 99%
“…In recent decades, an increasing amount of data has become available from laboratory studies focusing on the frictional properties of natural fault rocks, or their simulated (crushed and sieved) equivalents, sampled from seismically active upper crustal terrains across the globe (Carpenter et al, , ; Chen et al, ; Collettini et al, ; Ikari et al, ; Niemeijer & Collettini, ; Scuderi et al, ; Tembe et al, ; Verberne et al, ; Zhang & He, ) and from hydrocarbon reservoir systems being considered for geological storage of CO 2 (Pluymakers et al, ; Samuelson & Spiers, ). These studies have shown that the frictional strength of such fault rocks and its slip rate dependence, hence potential for velocity weakening or unstable seismogenic slip in the rate and state friction (RSF) approach to fault mechanics (Dieterich, , ; Marone, ; Ruina, ; Scholz, , ), primarily depend on fault rock composition and true, in situ (pore) pressure and temperature conditions.…”
Section: Introductionmentioning
confidence: 99%